Analysis of Service Quality and Satisfaction of Outpatient Loyalty in Treatment at Grogol Health Center, Kediri Regency - Olivia Agtri Octarita Putri Setiawan; Ema Mayasari (Journal of Hospital Management and Services, 2021)
One of the conditions that indicate the problem of service quality at the Grogol Health Center UPTD, Kediri Regency is the complaint from the health service users who are targeted are the attitudes and actions of doctors, nurses, administration and service slowness, inadequate drug supplies, facilities and infrastructure in the patient waiting room and medical equipment. The purpose of this study was to analyze the effect of service quality and satisfaction on the loyalty of outpatients in seeking treatment at the Grogol Health Center, Kediri Regency. The design of this study was an observational quantitative study with a cross-sectional approach with the focus of the study directed at analyzing the effect of service quality and satisfaction on the loyalty of outpatients in seeking treatment at the Grogol Health Center, Kediri Regency with a population of 510 respondents and a sample of 120 respondents taken using the Accidental Sampling technique. The findings showed that almost half of the respondents had a sufficient category of service quality of 57 respondents (47.5%). Most respondents had satisfaction in the moderate category of 75 respondents (62.5%). And most respondents had a moderate category of loyalty of 74 respondents (61.7%). The results of the study using Multiple Linear Regression Test showed that with a p-value of 0.000 <0.05, H1 was accepted, so it was concluded that simultaneously there was an influence of service quality and satisfaction on the loyalty of outpatients in seeking treatment at the Grogol Health Center, Kediri Regency with an influence of 80.6%. Outpatients can utilize the available health facilities and provide constructive criticism so that services can be developed even better.